2006
DOI: 10.1111/j.1574-6968.2006.00183.x
|View full text |Cite
|
Sign up to set email alerts
|

Effect of thecrpmutation on the utilization of transferrin-bound iron byVibrio vulnificus

Abstract: Cyclic AMP-cAMP receptor protein (CRP) complex plays an essential role in the global regulation of Vibrio vulnificus virulence. We found that growth retardation of V. vulnificus caused by mutation of the crp gene encoding CRP was exacerbated under iron-limited conditions. Accordingly, we investigated the effect of crp mutation on the expression of the vulnibactin-mediated iron-uptake system and the ability of V. vulnificus to utilize transferrin-bound iron, and thus to grow in cirrhotic ascites, a human ex viv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 23 publications
1
21
0
Order By: Relevance
“…CRP, which is a central regulator of energy (catabolic) metabolism, would make expression of the heme uptake protein metabolically coordinated, such that the acquired iron in cells should be used in the most efficient way as a cofactor or as a prosthetic group for essential enzymes involved in energy metabolism. Indeed, CRP regulation has also been observed in the synthesis of the V. vulnificus VuuA, a vulnibactin receptor protein (5). This metabolically coordinated acquisition and effective utilization of iron, one of the most limited resources, would facilitate establishing and maintaining infection and would be crucial for the overall success of the organism during pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…CRP, which is a central regulator of energy (catabolic) metabolism, would make expression of the heme uptake protein metabolically coordinated, such that the acquired iron in cells should be used in the most efficient way as a cofactor or as a prosthetic group for essential enzymes involved in energy metabolism. Indeed, CRP regulation has also been observed in the synthesis of the V. vulnificus VuuA, a vulnibactin receptor protein (5). This metabolically coordinated acquisition and effective utilization of iron, one of the most limited resources, would facilitate establishing and maintaining infection and would be crucial for the overall success of the organism during pathogenesis.…”
Section: Discussionmentioning
confidence: 99%
“…cAMP is generated through the cleavage of ATP by adenylate cyclase (encoded by cya in V. vulnificus [71]) and functions by binding the CRP, which then binds DNA to influence gene expression. Several putative virulence factors of V. vulnificus have been shown to be under the regulation of cAMP/CRP, including hemolysin, metalloprotease, and an iron acquisition system (5,19,21,48,49,71). Mutation of cya dramatically reduced hemolysin production and cytotoxicity to HeLa cells, and further examination revealed cAMP to be a primary regulator of hemolysin activity, with CRP binding to the vvhA promoter region and activating its transcription (19,71).…”
Section: Virulence Regulationmentioning
confidence: 99%
“…[4][5][6][7][8][9] Most recently, it has been demonstrated that the IUSs are under the positive control of cyclic AMP-receptor protein. 10,11) Quorum sensing (QS) is a process of bacterial cell-to-cell communication involving the production and detection of extracellular signaling molecules called autoinducers (AIs), and allows populations of bacteria to collectively control gene expression, and thus synchronize group behavior for better survival. Particularly, AI-2 is considered to be universal language for interspecies communication.…”
mentioning
confidence: 99%